Economic value of nature - Żylicz, Tomasz (Journal of Public Governance, 2018)
The paper uses the classic definition of economics as a science of making choices, and it defines economic value as the proportion people apply when they exchange one good for another. Goods provided by nature are exchanged too, but usually, unlike many other goods, they are not traded in markets, and so their values are difficult to ascertain. Nevertheless, over the last couple of decades economists have developed a number of methods to measure their values. The paper refers to valuation results presented in international literature, and discusses similar attempts carried out in Poland. It stresses that such valuations should be based on real decisions made by people even if their choices seem unreasonable and poorly thought through.